Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2478/acb-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord stem cells – the discovery, history and possible application

Abstract: Stem cells are now one of the most extensively studied fields in experimental medicine. Although embryonic stem cells (ESCs) have the capability to differentiate into lineages derived from all three primary germ layers, their use remains ethically controversial. Mesenchymal stromal cells’ (MSCs) utilization is not burdened with such concerns. MSCs were primarily characterized as fibroblastic cells from bone marrow stroma, with the ability to adhere to plastic and form clonogenic colonies (CFU-Fs – colony-formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Adult progenitor cells, such as those derived from the bone marrow, have been effectively used in treatment of hematopoiesis-associated diseases (e.g., leukemia) since the 1970s [9,10]. Adult stem cells present a range of advantages over their pluripotent counterparts, such as their ready availability in the adult organism, a narrowed range of differentiation lineages, limiting the possibility of malignant development after implantation, and the possibility of collection without major surgical procedures [11][12][13][14][15]. Furthermore, a significant amount of recent research, especially regarding the treatment of bone-and cartilage-related diseases, focuses on adipose-derived stem cells (ASCs) [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Adult progenitor cells, such as those derived from the bone marrow, have been effectively used in treatment of hematopoiesis-associated diseases (e.g., leukemia) since the 1970s [9,10]. Adult stem cells present a range of advantages over their pluripotent counterparts, such as their ready availability in the adult organism, a narrowed range of differentiation lineages, limiting the possibility of malignant development after implantation, and the possibility of collection without major surgical procedures [11][12][13][14][15]. Furthermore, a significant amount of recent research, especially regarding the treatment of bone-and cartilage-related diseases, focuses on adipose-derived stem cells (ASCs) [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, umbilical cord MSCs express the NANOG, Rex-1, and Sox-2 pluripotency gens. However, the expression of Oct-3/4, SSEA-3, SSEA-4, STRO-1, Tra-1-60, and Tra-1-81 is uncertain due to the contrary results of previous studies [ 208 , 209 , 210 , 211 ]. Similar to other subpopulations of perinatal MSCs, umbilical cord-derived MSCs possess high plasticity, and, under specific environmental conditions, could differentiate into all germ layer derivatives [ 227 , 228 , 229 , 230 , 231 ].…”
Section: Mesenchymal Stem/stromal Cells Derived From Human and Animal Perinatal Tissuesmentioning
confidence: 81%
“…In the literature, it has also been reported that hUC-WJ-MSCs express TRA-1-60, TRA-1-81, SSEA-1, and SSEA-4, even if their expression is questionable due to the discordant and uncertain results. As pluripotent stem cell markers, hUC-WJ-MSCs feature NANOG, Rex-1, and Sox-2 [133][134][135][136]. Like other populations of perinatal MSCs, UC-MSCs can differentiate into cells belonging to all germ layer derivatives [137,138].…”
Section: Umbilical Cord-derived Evsmentioning
confidence: 99%